A model of assistance of PLHIV (people with HIV AIDS) through social rehabilitation at the bina muda gemilang foundation Tangerang district - Sholih Sholih (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
This research was conducted to achieve the following specific objectives: (a) describe the implementation of the assistance program for People with HIV AIDS (ODHA) at the Bina Muda Gemilang Foundation; (b) obtain data on the effectiveness of fostering the assistance program for People with HIV AIDS (ODHA) at the Bina Muda Gemilang Foundation; and (c) Obtain data on the implementation and evaluation of the rehabilitation of people with HIV/AIDS at the Bina Muda Gemilang Foundation. The research method that will be used in this study is qualitative research because it will emphasize social rehabilitation for PLWHA (people living with HIV/AIDS) in an effort to formulate social rehabilitation assistance for PLWHA. Using a qualitative method, it will thoroughly examine the conditions of PLWHA or the profile of PLWHA and will examine in more depth the problems and needs of PLWHA to further formulate the assistance to be provided. Implementing the PLWHA assistance program by the Bina Muda Gemilang Foundation is carried out for High-Risk Groups of contracting HIV/AIDS (CSWs, Waria, Gay and IDU's, and Male Customers of sex). The effectiveness of the fostering of the PLWHA assistance program carried out by the Bina Muda Gemilang Foundation is carried out through the process of preparing assistance in an effort to prevent and handle HIV/AIDS cases. The implementation of rehabilitation for PLWHA is carried out in outreach to key populations/groups prone to contracting HIV/AIDS (Women Sex Workers, Transgenders, Gays, Male Customers of Sex and Injecting Drug Users). while participating with the assistance of the Bina Muda Gemilang Foundation. Abstrak: Penelitian ini dilakukan untuk mencapai tujuan khusus sebagai berikut: (a) mendeskripsikan penyelenggaraan program pendampingan Orang Dengan HIV AIDS (ODHA) di Yayasan Bina Muda Gemilang; (b) memperoleh data tentang efektivitas pembinaan program pendampingan Orang Dengan HIV AIDS (ODHA) di Yayasasan Bina Muda Gemilang; dan (c) Memperoleh data tentang pelaksanaan dan evaluasi dari rehabilitasi Orang Dengan HIIV AIDS di Yayasan Bina Muda Gemilang. Metode penelitian yang akan dipakai dalam studi ini adalah penelitian kualitatif, karena akan menekankan pada Rehabilitasi Sosial Terhadap ODHA (orang dengan HIV/AIDS) dalam upaya merumuskan pendampingan rehabilitasi sosial terhadap ODHA. Dimana dengan menggunakan metode kualitatif, akan secara dalam mengkaji kondisi ODHA atau profil ODHA serta secara lebih mendalam akan dikaji permasalahan dan kebutuhan para ODHA untuk lebih lanjut dirumuskan pendampingan yang akan diberikan. Penyelenggaraan program pendampingan ODHA yang dilakukan oleh Yayasan Bina Muda Gemilang dilakukan pada Kelompok Resiko Tinggi tertular HIV/AIDS (PSK, Waria,Gay dan IDU’s, dan Pria Pelanggan seks). Efektivitas pembinaan program pendampingan ODHA yang dilakukan oleh Yayasan Bina Muda Gemilang dilakukan melalui proses persiapan pendampingan dalam upaya mencegah dan menangani kasus HIV/AIDS.  Pelaksanaan rehabilitasi ODHA dilakukan dalam penjangkauan populasi kunci /Kelompok rentan tertular HIV/AIDS (Wanita Pekerja Seks, Waria, Gay, Lelaki pelanggan Seks dan Pengguna Narkoba Suntik.dan evaluasi rehabilitasi ODHA merupakan proses yang digunakan untuk mengukur tingkat kegagalan, keberhasilan dan kemajuan dari dampingan selama mengikuti pendampingan dari Yayasan Bina Muda Gemilang.